An extended stellar halo discovered in the Fornax dwarf spheroidal using Gaia EDR3. Issue 3 (14th March 2022) - Yang, Yanbin; Hammer, François; Jiao, Yongjun; Pawlowski, Marcel S
ABSTRACT: We have studied the extent of the Red Giant Branch stellar population in the Fornax dwarf spheroidal galaxy using the spatially extended and homogeneous data set from Gaia EDR3. Our pre-selection of stars belonging to Fornax is based on their proper motions, parallaxes, and colour–magnitude diagram. The latter criteria provide a Fornax star sample, which we further restrict by colour and magnitude to eliminate contaminations due to either Milky Way stars or QSOs. The precision of the data has been sufficient to reach extremely small contaminations (0.02–0.3 per cent), allowing us to reach to a background level 12 magnitudes deeper than the central surface brightness of Fornax. We discover a break in the density profile, which reveals the presence of an additional component that extents 2.1 degree in radius, i.e. 5.4 kpc, and almost seven times the half-light radius of Fornax. The extended new component represents 10 per cent of the stellar mass of Fornax, and behaves like an extended halo. The absence of tidally elongated features at such an unprecedented depth (equivalent to 37.94 ± 0.16 mag arcsec −2 in V-band) rules out a possible role of tidal stripping. We instead suggest that Fornax is likely at first infall, and has lost its gas very recently, which consequently leads to a lack of gravity implying that residual stars have spherically expanded to form the newly discovered stellar halo of Fornax.